The THE EFFECT OF PHASE II CARDIAC REHABILITATION EXERCISE ON FUNCTIONAL CAPACITY IN PATIENTS AFTER CORONARY ARTERY BYPASS SURGERY (CABG): PENGARUH LATIHAN REHABILITASI JANTUNG FASE II TERHADAP KAPASITAS FUNGSIONAL PADA PASIEN PASCA BEDAH PINTAS ARTERI KORONER - Lilis Suhaini; Tri Mustikowati; Widanarti Setyaningsih (Politeknik Kesehatan Kemenkes RI Jakarta I, 2026)
Coronary heart disease often requires Coronary Artery Bypass Grafting (CABG). Postoperatively, patients frequently experience declined functional capacity due to immobilization and pain, hindering recovery. This study aims to evaluate the effect of a Phase II cardiac rehabilitation exercise program on improving functional capacity in post-CABG patients. A quantitative analytical observational approach was used with a prospective cohort design involving a single group. The sample consisted of 40 postoperative patients who completed 12 sessions of Phase II cardiac rehabilitation, including aerobic warm-ups, static cycling (25 watts for 10 minutes), and treadmill or track walking. Functional capacity was measured using the Six-Minute Walk Test (6MWT) and Metabolic Equivalents (METs), converted via the Cahalin formula before and after the intervention. The findings showed a significant increase in METs after the intervention (p = 0.023; α < 0.05), with most patients improving from the moderate category (4–6 METs) to the good (>6–8 METs) and very good (>8 METs) categories. Statistical analysis using the Wilcoxon test yielded a Z-value of -2.271 (p = 0.023), indicating significant functional capacity improvement. Phase II cardiac rehabilitation is effective in enhancing functional capacity in post-CABG patients. Active participation is recommended for ongoing recovery.